2016
DOI: 10.1038/tp.2016.46
|View full text |Cite
|
Sign up to set email alerts
|

Maternal mid-pregnancy C-reactive protein and risk of autism spectrum disorders: the early markers for autism study

Abstract: Maternal pregnancy levels of the inflammatory marker C-reactive protein (CRP) has been previously associated with autism spectrum disorder (ASD) in the offspring. We conducted a population-based nested case–control study with 500 children with ASD, 235 with developmental delay (DD) and 580 general population (GP) controls to further investigate whether elevated CRP during pregnancy increases the risk of ASD. Maternal CRP concentration was measured in archived serum collected during 15–19 weeks of pregnancy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 44 publications
3
56
0
Order By: Relevance
“…A subsequent study found that maternal infections diagnosed in a hospital setting, presumably associated with more severe infections, were associated with an increased risk of ASD, while infections diagnosed in outpatient settings were not associated ASD (23). Quantification of cytokines, chemokines and other inflammatory markers obtained from archived maternal sera (24, 25) and amniotic fluid (26, 27) lends further support to the link between maternal infection and increased ASD risk, though studies have yielded mixed results (28, 29). Although there is a clear need for additional epidemiological studies, the current data suggest that, at least for a subset of women, exposure to infection during pregnancy may increase the risk of ASD or other CNS disorders (30, 31).…”
Section: Prenatal Immune Challenge In Humansmentioning
confidence: 88%
“…A subsequent study found that maternal infections diagnosed in a hospital setting, presumably associated with more severe infections, were associated with an increased risk of ASD, while infections diagnosed in outpatient settings were not associated ASD (23). Quantification of cytokines, chemokines and other inflammatory markers obtained from archived maternal sera (24, 25) and amniotic fluid (26, 27) lends further support to the link between maternal infection and increased ASD risk, though studies have yielded mixed results (28, 29). Although there is a clear need for additional epidemiological studies, the current data suggest that, at least for a subset of women, exposure to infection during pregnancy may increase the risk of ASD or other CNS disorders (30, 31).…”
Section: Prenatal Immune Challenge In Humansmentioning
confidence: 88%
“…For example, Brown et al showed that higher levels of maternal CRP during first and early second trimester of pregnancy was associated with a diagnosis of ASD in children. In contrast, a similar study found that maternal CRP levels in mid‐pregnancy were lower in mothers of ASD children compared with controls . Koks et al reported that the observed association between maternal CRP and children's autistic traits was largely explained by sociodemographic and maternal health‐related factors.…”
Section: Commentmentioning
confidence: 90%
“…The pathogenesis of ASD is complex and controversial, and both nutritional and immune causes have been recently associated with this complex pathology (Hsiao 2013, Endreffy et al 2016, Fujiwara et al 2016, Zerbo et al 2016. Controversial issues arose from attempting to distinguishing between children's and adults ASD, and particularly Asperger syndrome with high functioning autism in adults, where language delays may be used to distinguish the two pathologies, as the poor performance on language tests also challenges the assumption that early language development in Asperger syndrome is essentially normal (Howlin 2003, Baron-Cohem andWheelwright 2004).…”
Section: Introductionmentioning
confidence: 99%